2012
DOI: 10.1016/j.seizure.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of refractory vs. medically controlled epilepsy patients with obstructive sleep apnea and their response to CPAP treatment

Abstract: This study confirms that OSA is common in epilepsy patients and treatment of OSA can improve seizure control in medically refractory cases. Patients with refractory epilepsy who have diabetes are more likely to have OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 42 publications
6
17
0
1
Order By: Relevance
“…Previous studies have also demonstrated that an improvement in seizure frequency in refractory epileptic patients is achieved with the treatment of OSAS [26,27]. The screening for SBD to recognize an altered nocturnal respiratory function in the medically refractory epilepsy population is particularly outstanding to set up early intervention strategies [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated that an improvement in seizure frequency in refractory epileptic patients is achieved with the treatment of OSAS [26,27]. The screening for SBD to recognize an altered nocturnal respiratory function in the medically refractory epilepsy population is particularly outstanding to set up early intervention strategies [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Among the common population, the incidence rate of sleep apnea is at least 3%, while polysomnography analysis of investigated epileptic patients revealed that the incidence rate of sleep apnea may be up to 70%. For epileptic patients, seizures may improve following the diagnosis and treatment of sleep apnea (9). Although Li et al (9) did not evaluate the correlation of apnea with epileptic seizures, decreased oxygen saturation may cause brain stimulation or chronic sleep deprivation, aggravating the epileptic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…For epileptic patients, seizures may improve following the diagnosis and treatment of sleep apnea (9). Although Li et al (9) did not evaluate the correlation of apnea with epileptic seizures, decreased oxygen saturation may cause brain stimulation or chronic sleep deprivation, aggravating the epileptic seizures. VPA is known to cause weight gain, which in turn is capable of aggravating sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…149 A double-blind, placebo-controlled crossover study showed pregabalin increased NREM 3, decreased NREM 1 sleep, and improved attention in 9 adults with well-controlled epilepsy and sleep-maintenance insomnia. 150 …”
Section: Pregabalin and Gabapentin May Improve Disturbed Sleep In Peomentioning
confidence: 99%